Esophageal Capsule Endoscopy for Screening Esophageal Varices among Japanese Patients with Liver Cirrhosis - Haruya Ishiguro; Shoichi Saito; Hiroo Imazu; Hiroyuki Aihara; Tomohiro Kato; Hisao Tajiri (Gastroenterology Research and Practice)
Purpose. Although esophageal capsule endoscopy (ECE) is reportedly useful in the diagnosis of esophageal varices (EV), few reports have described the benefits of this technique in Asian countries. The present paper evaluates the usefulness of ECE for diagnosing EV in Japanese patients with cirrhosis. Methods. We examined 29 patients with cirrhosis (20 males and 9 females; mean age 60 years; Child-Pugh classification A/B/C; 14/14/1) using ECE followed by esophagogastroduodenoscopy (EGD). High-risk EV were defined as F2 and/or RC2 and above. Results. The sensitivity and specificity of ECE for the diagnosis of high-risk EV were 92% and 80%, respectively. Conclusions. The findings showed that ECE is a highly sensitive method of diagnosing high-risk EV that requires endoscopic or pharmacological therapy. Thus, ECE might be a useful method for the screening and followup of EV in patients with cirrhosis.